Seagrass biodiversity at three marine ecoregions of Indonesia: Sunda Shelf, Sulawesi Sea, and Banda Sea - MUJIZAT KAWAROE; ADITYA HIKMAT NUGRAHA; JURAIJ JURAIJ; ILHAM ANTARIKSA TASABARAMO (Biodiversitas Journal of Biological Diversity, 2016)
Kawaroe M, Nugraha AD, Juraij, Tasabaramo IA. 2016. Identification of soybean genotypes adaptive and productive to acid soil agro-ecosystem. Biodiversitas 17: 585-591. Seagrass is one of the coastal ecosystems in marine ecoregions of Indonesia that has very important ecological and economical functions. This study aimed to illustrate the diversity of seagrass ecosystems through its distribution, coverage, and density, in three marine ecoregions of Indonesia, namely Sunda Shelf/SHS (Bintan Island/SHS-B and the Seribu Islands/SHS-S), Sulawesi Sea/SS (Talaud Island), and Banda Sea/BS (Tanimbar Islands). The study was conducted at 16 stations in SHS, 20 stations in SS, and 30 stations in BS. A line transect method was used. Three line transects (length 50m) were deployed ineach station perpendicular to the shoreline towards the sea with a distance of 20 meters between transect lines. In each line transect, quadrate transects were placed (0.5mx0.5m) along the line, alternating left and right line up to the edge. Species identification and seagrass density were calculated in each quadrate transect. Similarity indexes were calculated and analyzed between ecoregion on seagrass coverage and abundance through dendrogram graphic. Results showed that 10 species of seagrass were found in three marineecoregions. In SHS-B, 10 species with a coverage cover of 61% were found and Thalassia hemprichii was of the highest abundance. In ShS-S, 6 species with a coverage cover of 37% were found and Enhalus acoroides species was of the highest abundance. In SS, 5 species with a coverage cover of 43% were found and Cymodocea rotundata was of the highest abundance. Finally, in BS, 7 species with coverage of 60% were found and Thalassia hemprichii was of the highest abundance. These results indicated that seagrass biodiversity found in 3 Indonesia marine ecoregions were still in a healthy condition. One of the implications of this healthy condition of seagrass was that the very important functions of seagrass as a habitat for economically important organisms and a food source for herbivores, particularly Dugong dugong, living in seagrass was still secured.